Potential of use of brown algae extract in the reproductive phenological stage of soybean (Research, Society and Development, 2022)
Based on the hypothesis that the algae extract applied during the development cycle of the soybean crop can stimulate plant growth, thus increasing productivity. The objective was to apply different doses of algae extract (Ascophyllum nodosum) in the reproductive stage of soybean, evaluating the influence on the plant's growth, physiological and yield parameters. The experiment was carried out in the experimentation area belonging to the company Tecno Nutrição Vegetal e Biotecnologia Ltda. - Rio Verde – GO, in a dystrophic Red Latosol (LVDf). The experimental design used was a randomized block, with 5 treatments and 4 replications, totaling 20 experimental plots. The treatments consisted of 5 doses of algae extract: T1) 0.0 L ha-1; T2) 0.5 L ha-1; T3) 1.0 L ha-1; T4) 1.5 L ha-1; T5) 2.0 L ha-1. Biometric variables were evaluated: plant height, number of nodes, number of leaves, number of branches and stem diameter; physiological: chlorophyll levels and; yields: mass of 100 grains and grain yield. Data were submitted to analysis of variance (p